Drivers of renewable technology adoption in the household sector - Anke Jacksohn; Peter Grösche; Katrin Rehdanz; Carsten Schröder (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Using representative household survey panel data from Germany, we undertake a simultaneous assessment of the importance of factors that have individually been found significant for the adoption of renewable energy systems but have never been tested jointly. These are sociodemographic and housing characteristics, environmental concern, personality traits, and economic factors, i.e. the expected costs of and revenue from the investment. Our results suggest that household decisions to invest in photovoltaic systems and solar thermal facilities are mainly driven by the economic factors. Taking account of sociodemographic and housing characteristics, environmental concern or personality traits has comparatively little relevance, while the quantitative nexus between the decision to invest and returns on the investment is robust to their inclusion.
Keywords: C25; D12; Q55; 330; renewable technology adoption; investment decision; solar energy; household sector